"ADe" A Sociolinguistic Analysis of a Relationship. Working Papers in Sociolinguistics, No. 69 - Schieffelin, Bambi B.; Southwest Educational Development Lab., Austin, TX. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1979)
Recent studies have documented the importance of a variety of contextualization cues such as intonation, voice quality, volume, and pitch in conversation. The appropriate use of and response to them presupposes that one has certain kinds of linguistic and sociocultural knowledge. There remains, however, the question of how children acquire this knowledge. As a step toward understanding this acquisition process, this paper discusses how children among the Kaluli people in New Guinea learn about making and responding to requests based on a strategy of appeal. The particular type of interaction under study is called "ade." The relationship denoted by "ade" is one of caring and nurturing, and is a most important one in the society. The correct use of the term "ade" is important in evoking the "ade" relationship. The different aspects of the "ade" relationship in the contexts in which it is used in family interactions are examined. This examination includes ways in which children are taught to respond to requests based on appeal as well as the difficulties small children have in using the "ade" term appropriately. Finally a myth is presented which provides a larger ethnographic perspective to what the mother is trying to create in the relationship between her children. (AMH)
Availability: Southwest Educational Development Laboratory, 211 East 7th Street, Austin, TX 78701.
Sponsoring Agency: National Inst. of Education (DHEW), Washington, DC.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Child Language; Children; Communication Research; Discourse Analysis; Interpersonal Relationship; Language Acquisition; Pragmatics; Sociolinguistics; Speech Communication; Verbal Development; New Guinea; Reports, Research